Comparative Translation Qualitty Of Religious Terms In Umberto Eco’s The Name Of The Rose - Mohamad Fauzi Agung Pamuji; Wiwin Indiarti; Arin Inayah (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2021)
This research is a comparative study of translation using descriptive qualitative approach. It aims at examining the quality (accuracy and acceptability levels) of religious terms translation of two translation works of an outstanding qualities novel written by Umberto Eco entitle The Name of the Rose. To be exact, this research airmed to: 1). Measure the translation accuracy and acceptability of religious terms in The Name of the Rose published by Jalasutra, 2). Measure the translation accuarcy and acceptability of religious terms in The Name of the Rose published by Bentang Pustaka, and 3). Describe the differences and similarities of the translation accuracy and acceptability of religious terms published by Jalasutra and Bentang Pustaka. The research data are religious terms found in The Name of the Rose which is collected using documentation method. The collected data are analyzed by using three following steps, 1). Comparing, 2). Describing and 3). Reporting. To assess translation accuracy and acceptability, the researcher used the translation quality assessment instruments by Prof. Mangatur Nababan. The research results that the translation accuracy and acceptability of The Name of the Rose published by Jalasutra and Bentang Pustaka are good. Both provide accurate translation of religious terms since they successfully translate 321 terms accurately. However, Bentang Pustaka translates 14 terms less accurately and 6 terms with inaccurate while Jalasutra translates 10 terms less accurately and 10 terms with inaccurate. The different quality of accuracy and acceptability was due to the translators’ different consideration between maintaining the accuracy and acceptability level or reaching high readability translation. The conclusion is that Bentang Pustaka provides better translation than Jalasutra.